Association and dose–response relationship of plasma magnesium with metabolic syndrome in Chinese adults older than 45 years - Yang, Jingxin; Cao, Yang; Zhang, Huidi; Hu, Yichun; Lu, Jiaxi; Wang, Rui; Feng, Jie; Yang, Lichen (Frontiers in Nutrition, 2024)
Purpose Magnesium (Mg) is an essential nutrient for the maintenance of vital physiological functions. Magnesium deficiency is associated with diseases such as obesity, type 2 diabetes mellitus (T2DM), and metabolic syndrome (MetS); however, conclusions have been inconsistent, and there is a particular lack of evidence regarding this association in Chinese population older than 45 years. This study aimed to assess the association between plasma magnesium and the risk of MetS and its components, the dose–response relationship, and the threshold effect relationship in a Chinese population involving older than 45 years. Methods A total of 2,101 individuals were randomly selected from the China Nutrition and Health Surveillance (CNHS) (2015–2017) by considering monitoring points. We used the joint statement of the International Diabetes Federation (IDF) in 2009 to define participants with MetS. The plasma magnesium was tested by inductively coupled plasma mass spectrometry (ICP-MS). The logistic regression and restricted cubic spline (RCS) models were used to analyze the association and dose–response relationship between plasma Mg and MetS and its components. Results Compared with the lowest quintile (Q1) for plasma Mg, the odds ratios (ORs) and 95% confidence intervals (95% CI) for MetS, impaired fasting glucose (IFG), hypertension, and triglyceride (TG) elevation at the highest quintile (Q5) were 0.419 (0.301, 0.583), 0.303 (0.221, 0.415), 0.446 (0.322, 0.618), and 0.526 (0.384, 0.720), respectively, with all p < 0.05. However, in the components of decreased high-density lipoprotein cholesterol (HDL-C) and central obesity, no trend toward lowering with higher plasma magnesium was observed (p = 0.717, p = 0.865). These associations were not altered by further adjustment for potential confounding variables, including age, gender, education, nationality, area, residence, body mass index (BMI), and heart rate. The RCS analysis showed that, when plasma magnesium was lower than 0.85 mmol/L, the curve was leveled off, and then, the curve showed a decreasing trend with the increase in plasma magnesium. Conclusion Therefore, plasma Mg was negatively associated with MetS and its components (including IFG, hypertension, and elevated TG) in people older than 45 years. In addition, plasma Mg greater than or equal to 0.85 mmol/L, which is higher than the commonly used threshold of 0.75 mmol/L, may be protective against MetS and its components (including elevated FPG, elevated blood pressure, and elevated TG). More prospective studies, such as randomized controlled trials, are necessary to confirm the effective impact of Mg on MetS and its components. Plasma Mg levels in the MetS population older than 45 years require attention.